﻿Expansion of the alien East Asian river prawn Macrobrachium nipponense (De Haan, 1849) in southwestern Ukraine and assessment of its commercial usage prospects - Sergii Bushuiev; Sergii Snigirov; Mikhail O. Son; Ievhen Sokolov; Genadiy Kharlov; Yuriy Kvach (Aquatic Invasions)
At this time East Asian river prawn Macrobrachium nipponense is present almost everywhere in the lower reaches of the Danube and Dniester basins, in the Danube-Dniester interfluves and water bodies to the east of the Dniester. Successful adaptation and favorable climatic conditions in recent years have provided a significant increase in the East Asian river prawn populations in the Danube and Dniester. High growth rates of M. nipponense have been observed in the Danube and Dniester. In these river basins, higher values of maximum body length of the prawn (males 115 mm, females 87 mm) than those recorded in the native range water bodies and the cooler water bodies of thermal power plants during introduction were recorded. In small shallow brackish-water reservoirs of the region (PSU 1.5–6.0) the growth rate of M. nipponense is significantly lower than in the freshwater Danube and Dniester deltaic zones. Female East Asian river prawn in such water bodies mature at a much smaller size. The egg-laying period of female M. nipponense in the Danube lasts from June to October. The peak of egg laying is observed in July and August. There have been reported cases of M. nipponense being affected by crustacean burn-spot disease. The prospect of organizing the fishing of M. nipponense in the Danube River has been determined. It is necessary to continue research to increase selectivity of fishing gears, determination of optimal terms of fishing, and places of installation of fishing gears.